Accuracy of additively manufactured zirconia four-unit fixed dental prostheses fabricated by stereolithography, digital light processing and material jetting compared with subtractive manufacturing. Issue 9 (September 2022) - Lüchtenborg, Jörg; Willems, Evita; Zhang, Fei; Wesemann, Christian; Weiss, Florian; Nold, Julian; Sun, Jinxing; Sandra, Fabien; Bai, Jiaming; Reveron, Helen; Chevalier, Jérôme; Spies, Benedikt C.
Abstract: Objective: To evaluate the manufacturing accuracy of zirconia four-unit fixed dental prostheses (FDPs) fabricated by three different additive manufacturing technologies compared with subtractive manufacturing. Methods: A total of 79 zirconia FDPs were produced by three different manufacturing technologies, representing additive (one stereolithography [aSLA] and one material jetting [aMJ] device, two digital light processing [aDLP1/aDLP2] devices) and subtractive manufacturing (two devices [s1/s2]), the latter serving as references. After printing, additively manufactured FDPs were debound and finally sintered. Subsequently, samples were circumferentially digitized and acquired surface areas were split in three Regions Of Interest (ROIs: inner/outer shell, margin). Design and acquired data were compared for accuracy using an inspection software. Statistical evaluation was performed using the root mean square error (RMSE) and nonparametric Kruskal-Wallis method with post hoc Wilcoxon-Mann-Whitney U tests. Bonferroni correction was applied in case of multiple testing. Results: Regardless the ROI, significant differences were observed between manufacturing technologies (P < 0.001). Subtractive manufacturing was the most accurate with no significant difference regarding the material/device (s1/s2, P > 0.054). Likewise, no statistical difference regarding accurary was found when comparing s2 with aMJ and aSLA in most ROIs (P > 0.085). In general, mean surface deviation was< 50 µm for s1/s2 and aMJ and< 100 µm for aSLA and aDLP2. aDLP1 showed surface deviations> 100 µm and was the least accurate compared to the other additive/subtractive technologies. Significance: Additive manufacturing represents a promising set of technologies for the manufacturing of zirconia FDPs, but not yet as accurate as subtractive manufacturing. Methodological impact on accuracy within and in between different additive technologies needs to be further investigated.